Dynamics of Linguistic Features of the Text About a Company in the English Language - A. A. Kharkovskaya; I. B. Krivchenko (Дискурс профессиональной коммуникации, 2022)
The development of online media and the growth of the number of Internet users provoke the rise of new forms and genres, which initially appeared in the English language. In the sphere of business, it has become essential to have a website, the main compo- nent of which is the “About Us” section. Minitexts placed in this section in the course of time changed their focus from being merely informative to becoming advertising. This transfer of its functional value has led to the change in structural and semantic features of the text. The research aims at analysing linguistic features of the texts of the type mentioned. The research seems to be relevant because it deals with the media discourse which offers new ways of promoting goods and services. Such new forms require scientific treatment of their structure and content. The scientific novelty of the study lies in treating the above-mentioned texts from the point of view of their dynamics. The authors claim that there has been a functional change in the texts under consideration from them being informative to becoming promotional which caused the changes in their structure, contents, and volume.